Research Progress on Human Thermal Comfort Models in Asymmetric Thermal Environments - Wu Qingqing; Liu Jianhua; Zhang Liang; Zhang Jiawen; Jiang Linlin (Zhileng xuebao)
Based on the classification criteria of thermal space models, human thermal physiological models, and human thermal psychological models, this paper gives a comprehensive review of human comfort research in an asymmetric environment. Thermal space models directly predict the objective and subjective response of humans using air conditioning and environmental parameters. Human thermal physiological models predict the physiological parameters of humans by studying active and passive physiological regulation in human bodies. Human thermal psychological models focus on the relationship between physiological parameters and subjective responses or on how the human body adapts to the thermal environment. Finally, the advantages and limitations of each model is summarized. The results show that the thermal space model has a significant relationship with the selected space structure; once the space structure changes, many of the relationships established by the model cannot be established, which is more valuable in the field of vehicle applications; most thermophysiological and thermopsychological models are not comprehensive or limited to specific environments, and only a few can address human responses to non-uniform and transient conditions through detailed body temperature regulation; the Berkeley thermal comfort model covers both thermophysiological and thermopsychological models, but its coupling simulation process is too complicated; while the equivalent temperature model has relatively low accuracy, it is more widely used due to its simple operation; adaptive model fully considers human subjective initiative, but its research is still in its infancy.